Automatic tool for the reconciliation of serious adverse events for pharmacovigilance: design and implementation of Reconciliaid - Sara Contu; Renaud Schiappa; Yann Chateau; Emmanuel Chamorey (Therapeutic Advances in Drug Safety)
Background: Reporting serious adverse events (SAEs) is crucial to reduce or avoid toxicities that can lead to major consequences for patient’s health due to treatments tested in clinical trials. Its exhaustiveness is often inadequate, and we observe discrepancies between data published by pharmacovigilance organizations and clinical databases. Objectives: While the process of reconciliation aims at reducing these differences, it remains a very time-consuming and imprecise task. We propose a tool to automate this process. Design: We have developed and tested Reconciliaid, an application that compares the SAEs of the databases of clinical trials collected according to a standard inspired by the Clinical Data Interchange Standards Consortium, and of pharmacovigilance collected according to the international standards ICH-E2B (R3). It generates a reconciliation file that indicates precisely what information does not coincide in the two databases to facilitate the identification of inconsistencies. Methods: Reconciliaid was tested to create 13 reconciliation files, containing 290 SAEs. We inspected these files to determine their ability in identifying the inconsistencies and compared the manual and semi-automated reconciliation time. Four users answered the System Usability Scale (SUS) to measure its usability. Results: The application identified all variables of interest in all reconciliations. Different formats and libraries were automatically harmonized, allowing a perfect identification of inconsistencies for all variables. The matching of the same SAE in the two databases was correct in 97.2% of the reconciliations. Reconciliaid is six times faster than the manual approach for senior data managers (range = 3–24 times). A novice data manager performed three reconciliations 4.8 faster with the help of Reconciliaid than manually (29 min vs 134 min) and with fewer mistakes. Mean SUS score was 92.5. Conclusion: Reconciliaid has a high level of usability, can increase the quality of reconciliation, and reduces considerably the reconciliation time, allowing to increase the frequency of reconciliation processes and to focus resources on patient safety and medical assessment.